2018
DOI: 10.2478/jce-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Particularities in Acute Myocardial Infarction – a Study on a Patient Cohort from North East Romania

Abstract: Introduction: Cardiovascular disease is the leading cause of death among women irrespective of race or ethnicity, and about half of these deaths are caused by coronary artery disease. Several studies have reported that cardiovascular diseases manifest themself with a delay of about 7–10 years in women and that they have higher in-hospital mortality. It has not yet been established whether female gender itself, through biological and sociocultural differences, represents a risk factor for early in-hospital mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Some of these networks have been proved to represent real life-saving therapies, as the implementation of primary revascularization in ST-elevation myocardial infarction (STEMI) within a well-organized system led to a spectacular reduction in STEMI-related mortality. [1][2][3] In an attempt to make the STEMI networks highly effi- 6 According to this study, fewer women than men presented to the hospital in the first 12 hours after angina onset. Interestingly, the authors also demonstrated that in women from this geographical area, coronary events began more frequently in the morning with atypical symptoms.…”
mentioning
confidence: 88%
“…Some of these networks have been proved to represent real life-saving therapies, as the implementation of primary revascularization in ST-elevation myocardial infarction (STEMI) within a well-organized system led to a spectacular reduction in STEMI-related mortality. [1][2][3] In an attempt to make the STEMI networks highly effi- 6 According to this study, fewer women than men presented to the hospital in the first 12 hours after angina onset. Interestingly, the authors also demonstrated that in women from this geographical area, coronary events began more frequently in the morning with atypical symptoms.…”
mentioning
confidence: 88%